Impact of Ball Burnishing Process on Residual stress distribution in Aluminium 2024 Alloy using Experimental and Numerical Simulation. Issue 1 (October 2021) - Harish,; Shivalingappa, D.; Raghavendra, N; Ganesh, V
Abstract: Deep ball burnishing is surface enhancement process is specifically used to induce compressive residual stress in material sub surface. In this investigation deep ball burnishing surface treatment process was carried out on the periphery of Al 2024 alloy and induced beneficial compressive residual stress was determined by X-Ray Diffraction method. In this work explicit module of the FE-Code ABAQUS-6.17 was used to model the ball burnishing process and analysis is carried out to determine the residual stresses in Aluminium 2024 Alloy by changing instantaneously process variables like burnishing passes and pressure. Comparison was made among experimental and results obtained from FEA, it was observed that there is well agreement between the FE Results and experimental results. Also the results revealed the impact of deep ball burnishing process parameters on distribution of beneficial compressive residual stress.